Improving students’ adjectives vocabulary knowledge using games / Wahidah Abdul Halim - Abdul Halim, Wahidah (2015)
This research is a study about improving adjective vocabulary mastery and knowledge through games. This research is to investigate and determine whether games can improve the student’s adjective vocabulary knowledge. Vocabulary is the language aspect that very important for studying English. But, most of the students in primary school especially in the rural areas get much difficulty to learn English especially in vocabulary. Therefore, the researcher would like to try using game methods to solve some problems that experienced by most by most students. The respondents of the research are the year three students of primary schools in Sekolah Kebangsaan Felda Jerangau Barat, Terengganu. There are 28 participants involved in the study. Participants are twelve (12) males and sixteen (16) females of 3 Bestari. To answer the research questions, the researcher uses pre-test and post-test in the research as well as an observation checklist to examine the effectiveness of using games for teaching vocabulary in ESL classroom. Based on the result of the pre-test and posttest, the means have increasedfrom 47.07 to 76.82. The analysis determines that using games approach can improve the students ’ performance and arouse their interest in learning vocabulary through fun and interesting learning environment.